REDESAIN MASJID AL- MUHAJIRIN DENGAN KONSEP GREEN SEBAGAI FASILITAS IBADAH DAN PENDIDIKAN - Samsu Hendra Siwi, (Jurnal Bakti Masyarakat Indonesia, 2023)
The location of the Al-Muhajirin mosque is in the Pulo Sirih Housing area as a social facility for the surrounding community. This mosque is a Muslim worship facility in the neighborhood of RT 01 RW 13, Pekayon Jaya Village, South Bekasi District. was founded in 1989. This mosque is on land + 671.5 m2. This mosque has never been renovated. The mosque building is 105 m2, with TPA and an ablution place. Partners (Management of the Suluk Mimbar Abadi Foundation) submitted a request for assistance to Tarumanagara University to assist with mosque design drawings as a service to the community through PKM. Some of the things that Mitra wants related to the design of the mosque later are as follows: the building can become an icon in the area; the building and its environment use tropical and modern architectural concepts; the need for space that can accommodate religious, social, and economic activities. The design method used by infill is because the partners want the old building to be maintained by providing novelty to several parts and developments. The green concept is a solution for saving energy with maximum natural ventilation and natural lighting. Besides that, the mosque is an education center, so this new design has the concept of environmental education by accommodating programs that are environmentally sound and food security by utilizing the rooftop as a roof garden. The design results from this PKM answer the needs of partners in the development of mosques with green and old-new concepts and the development of educational places ABSTRAK: Lokasi masjid Al-Muhajirin berada di dalam satu wilayah Perumahan Pulo Sirih sebagai fasilitas sosial bagi masyarakat sekelilingnya. Masjid ini merupakan fasilitas ibadah umat muslim di lingkungan RT 01 RW 13, Kelurahan Pekayon Jaya, Kecamatan Bekasi Selatan. didirikan pada tahun 1989. Masjid ini berada di tanah + 671,5 m2. Masjid ini belum pernah mengalami renovasi. Bangunan masjid seluas 105 m2, TPA dan tempat wudhu. Mitra (Pengurus Yayasan Suluk Mimbar Abadi) pengajuan permintaan bantuan kepada Universitas Tarumanagara untuk memberikan bantuan gambar desain masjid sebagai sebuah pelayanan kepada masyarakat melalui PKM. Beberapa hal yang diinginkan Mitra yang terkait dengan desain masjid nantinya adalah sebagai berikut: bangunan bisa sebagai ikon di daerahnya; bangunan dan lingkungannya memakai konsep arsitektur tropis dan modern; kebutuhan ruang yang dapat menampung kegiatan ibadah, sosial dan ekonomi. Metoda desain yang dipakai infill karena mitra menginginkan bangunan lama tetap dipertahankan dengan memberikan kebaruan pada beberapa bagian dan pengembangan. adalah Konsep green menjadi solusi untuk hemat energi dengan desain pengudaraan alam dan pencahayaan alam yang maksimal. Di samping itu masjid sebagai pusat pendidikan maka desain baru ini berkonsep pendidikan cinta lingkungan dengan mewadahi program yang berwawasan lingkungan dan ketahanan pangan dengan pemanfaatan rooftop sebagai roof garden. Hasil desain dari PKM ini menjawab kebutuhan mitra dalam pengembangan masjid dengan konsep green dan lama-baru dan sebagai pengembangan tempat pendidikan.